What are the combined effects of negative emotions and illness cognitions on self-care in people with type 2 diabetes? A longitudinal structural equation model. Issue 7 (2nd July 2016) - Hudson, Joanna L.; Bundy, Christine; Coventry, Peter; Dickens, Chris; Wood, Alex; Reeves, David
Abstract : Objective: To explore whether negative emotions mediate the effect of diabetes cognitions on diabetes self-care and conversely whether diabetes cognitions mediate the effect of negative emotions on diabetes self-care. Design: Longitudinal observational study in adults with type 2 diabetes. Main outcome measures: Self-reported depression and anxiety (Diabetes Wellbeing Questionnaire), cognitions (Illness Perceptions Questionnaire-Revised; Beliefs about Medicines Questionnaire), and diabetes self-care (Summary of Diabetes Self-Care Activities Scale) were completed at baseline and six months. Analyses used structural equation modelling. Results: Baseline medication concerns were associated with elevated symptoms of depression and anxiety at follow-up, but emotions did not mediate medication concern's effect on diabetes self-care. Baseline depression and anxiety symptoms were associated with specific diabetes cognitions over time, but these cognition domains did not mediate emotion's effect on diabetes self-care. Personal control remained independent of emotions and was associated with diabetes self-care over time. Conclusions: Negative emotions did not act directly or alongside cognitions to influence diabetes self-care. The reciprocal relationship between diabetes cognitions and emotions suggests cognitive restructuring, in addition to other mood management intervention techniques would likely improve the emotional wellbeing of adults with type 2 diabetes. Likewise, personal control beliefs are likely important intervention targets for improving self-care.